2012
DOI: 10.1128/jvi.02439-12
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Potential of Subpopulations of CD8+T Cells in HIV-1-Infected Elite Suppressors

Abstract: Elite controllers or suppressors (ES) are HIV-1-infected individuals who suppress viral replication to clinically undetectable levels without antiretroviral therapy. Understanding the mechanisms by which ES control viral replication may prove informative for the design of a therapeutic vaccine. Qualitative differences in the CD8 ؉ T cell response have been implicated in control. Therefore, we isolated CD8 ؉ T cells from ES and characterized the ability of sorted memory and activation subpopulations to control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 58 publications
3
45
1
1
Order By: Relevance
“…This is contrast to the findings of our prior studies, where we saw no inhibition of viral replication in CD4 ϩ T cells by CD8 ϩ T cells from healthy donors (11,35,59). It is possible that this inhibition may represent an innate immune response or the development of an adaptive response during the 7-day period of coculture of infected macrophages and CD8 ϩ T cells.…”
Section: A) C)contrasting
confidence: 56%
See 1 more Smart Citation
“…This is contrast to the findings of our prior studies, where we saw no inhibition of viral replication in CD4 ϩ T cells by CD8 ϩ T cells from healthy donors (11,35,59). It is possible that this inhibition may represent an innate immune response or the development of an adaptive response during the 7-day period of coculture of infected macrophages and CD8 ϩ T cells.…”
Section: A) C)contrasting
confidence: 56%
“…Strong CD8 ϩ T cell responses to HIV-1-infected CD4 ϩ T cells have been documented in many ESs; thus, we examined the ability of unstimulated primary ES CD8 ϩ T cells to suppress viral replication in MDMs using a variation of a previously described inhibition assay (4,35). The responses elicited by the CD8 ϩ effectors were divided into three categories on the basis of the distribution of the degree of inhibition observed in all the patients studied.…”
Section: Resultsmentioning
confidence: 99%
“…The high cytotoxic potential of HIV-specific CD8 ϩ T cells has also been reported by others after in vitro culture with HIV antigens (15,48,49). However, our first report described only 11 subjects, the majority of whom expressed HLA-B*57 or HLA-B*27 or both.…”
Section: Discussionmentioning
confidence: 53%
“…Accordingly, Buckheit et al have previously demonstrated that HIV-specific CD8 ϩ T cell subsets exhibit different in vitro suppressive activities depending on the time point considered: terminally differentiated cells were more suppressive at an early stage, whereas a less differentiated fraction exhibited an equally suppressive function at later time points (33). Polyfunctionality, a marker of efficient T cell responses, may thus also rely on the diversity of CD8 ϩ T cell differentiation ensuring a large timescale of cytotoxic responses balancing from immediate to late induced cytotoxic activity.…”
Section: Previous Reports Have Suggested That Hiv-specific Cd8mentioning
confidence: 99%